Sealing ability of MTA, CPM, and MBPc as root-end filling materials: a bacterial leakage study (Journal of Applied Oral Science, 2016)
Objectives To evaluate the sealing ability of three root-end filling materials (white MTA, CPM, and MBPc) using an Enterococcus faecalis leakage model. Material and Methods Seventy single-root extracted human teeth were instrumented and root-ends were resected to prepare 3 mm depth cavities. Root-end preparations were filled with white MTA, CPM, and MBPc cements. Enterococcus faecalis was coronally introduced and the apical portion was immersed in BHI culture medium with phenol red indicator. The bacterial leakage was monitored every 24 h for 4 weeks. The statistical analysis was performed using the Wilcoxon-Gehan test (p